2(x-6)-8x=-36

Simple and best practice solution for 2(x-6)-8x=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-6)-8x=-36 equation:


Simplifying
2(x + -6) + -8x = -36

Reorder the terms:
2(-6 + x) + -8x = -36
(-6 * 2 + x * 2) + -8x = -36
(-12 + 2x) + -8x = -36

Combine like terms: 2x + -8x = -6x
-12 + -6x = -36

Solving
-12 + -6x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -6x = -36 + 12

Combine like terms: -12 + 12 = 0
0 + -6x = -36 + 12
-6x = -36 + 12

Combine like terms: -36 + 12 = -24
-6x = -24

Divide each side by '-6'.
x = 4

Simplifying
x = 4

See similar equations:

| 7n^2=252 | | .5a+8.75=13.25+2a | | 8x-24-x+3=0.7 | | 2x-(x+4)=-5-3x+1 | | 9-p=2 | | X-1/9=5/8 | | 3x-5+6x=40 | | -13-(-47)=x/7 | | -5(x-5)+2=27 | | 8.95+1.50=26.95 | | -1.4x=2.67 | | 23/20y=46 | | 0=16x^2-760 | | 6p=-26 | | 5x+4-x-1= | | 3b-15=12 | | 40x^2+2x-30=0 | | =10x^2+3x-1 | | 3(3z-2)-3(2-2z)=6 | | 4x^2=75 | | 4=-5x+4(x+4) | | 10y+5x=12 | | 102+4n=1486 | | -2a+6=2a-2 | | 8x^2-17x-671=0 | | -19.76x=-92.57x | | -6k-3=33 | | 9x-21=35-1 | | 227x=1052x | | 3x+2=3(5)+2 | | .53a=.06a+.4 | | -19.76x+227=-92.57+1052 |

Equations solver categories